2017
DOI: 10.1038/s41598-017-05699-x
|View full text |Cite
|
Sign up to set email alerts
|

Handheld Co-Axial Bioprinting: Application to in situ surgical cartilage repair

Abstract: Three-dimensional (3D) bioprinting is driving major innovations in the area of cartilage tissue engineering. Extrusion-based 3D bioprinting necessitates a phase change from a liquid bioink to a semi-solid crosslinked network achieved by a photo-initiated free radical polymerization reaction that is known to be cytotoxic. Therefore, the choice of the photocuring conditions has to be carefully addressed to generate a structure stiff enough to withstand the forces phisiologically applied on articular cartilage, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
147
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 177 publications
(164 citation statements)
references
References 32 publications
(38 reference statements)
9
147
0
Order By: Relevance
“…Fedorovich et al demonstrated that the combination of UV light with Irgacure 2959 resulted in the highest cytotoxicity compared with the two modalities alone . Similar results were generated with LAP and RB indicating that the PI toxicity is drastically exacerbated by photoactivation …”
Section: Sources Of Cytotoxicity and Genotoxicitymentioning
confidence: 79%
See 4 more Smart Citations
“…Fedorovich et al demonstrated that the combination of UV light with Irgacure 2959 resulted in the highest cytotoxicity compared with the two modalities alone . Similar results were generated with LAP and RB indicating that the PI toxicity is drastically exacerbated by photoactivation …”
Section: Sources Of Cytotoxicity and Genotoxicitymentioning
confidence: 79%
“…In cartilage tissue engineering, the coaxial method was found to be superior to the monoaxial configuration where cells are embedded throughout the hydrogel and exposed to the toxic photoinitiation process triggered by a fast high irradiance exposure to UV light. In Duchi et al, the cytotoxicity of bioprinted hADSCs upon 10 second irradiation with 365 nm at 700 mW/cm 2 was found to be negligible, when cells were segregated from the PI, and the viability of UV only irradiated cells was comparable to the nonirradiated control group throughout 7 days . Moreover, high levels of cell survival immediately after printing and crosslinking with an increase in cell number 10 days following extrusion.…”
Section: Strategies To Reduce Cytotoxicitymentioning
confidence: 98%
See 3 more Smart Citations